Premonitory urge in tic disorders – a scoping review - Wohlgemuth, John B.; Watson, Kelly H.; Gill, Kayce D.; Isaacs, David A. (Frontiers in Psychiatry, 2025)
IntroductionPremonitory urges are uncomfortable bodily sensations preceding tics. They are highly prevalent, frequently bothersome, and increasingly recognized as a central phenotypic feature in tic disorder populations. This scoping review aimed to systematically consolidate published knowledge and identify knowledge gaps regarding premonitory urges in primary tic disorders.MethodsSearch strategies were deployed in five databases and five topic-relevant journals. Two independent reviewers screened all candidate abstracts against predefined inclusion criteria. One hundred and fifty-five articles were included in the scoping review. The same two reviewers independently extracted and consolidated pertinent data from included articles.ResultsMultiple methods for assessing premonitory urge were identified, each with strengths and weaknesses. The subjective quality of premonitory urges varies between individuals, with increased prevalence of a “not just right” urge quality in individuals with comorbid obsessive-compulsive disorder. Awareness of premonitory urge appears to arise several years after tic-onset, yet many individuals perceive their tics as voluntary responses to premonitory urges. Premonitory urges and tics are temporally coupled in real time, but premonitory urge severity and tic severity, as assessed by clinical scales, are not consistently associated. The mechanistic and developmental relationship between premonitory urges and tics remains unclear. Data are limited on premonitory urge response to treatment, but several promising interventions were identified. The insula and supplementary motor area are the neuroanatomical structures most strongly implicated in emergence of the premonitory urge.DiscussionKnowledge of the clinical characteristics, measurement, and neural mechanisms of premonitory urge has advanced considerably in recent years, but important knowledge gaps remain in each of these domains. Addressing these knowledge gaps will be key to developing effective interventions for premonitory urge.Systematic Review RegistrationOpen Science Framework (OSF) https://doi.org/10.17605/OSF.IO/WT43Z.